Interreligious Studies: Dispatches from an Emerging Field, edited by Hans Gustafson - Mirza, Younus Y. (Interreligious studies and intercultural theology, 2021)
Interreligious Studies: Dispatches from an Emerging Field, edited by Hans Gustafson. Baylor University Press, 2020. 295 pp., Hb., £35. ISBN 978-1481312547